2019
DOI: 10.1007/s10544-019-0412-y
|View full text |Cite
|
Sign up to set email alerts
|

A review of microsampling techniques and their social impact

Abstract: Conventional skin and blood sampling techniques for disease diagnosis, though effective, are often highly invasive and some even suffer from variations in analysis. With the improvements in molecular detection, the amount of starting sample quantity needed has significantly reduced in some diagnostic procedures, and this has led to an increased interest in microsampling techniques for disease biomarker detection. The miniaturization of sampling platforms driven by microsampling has the potential to shift disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 104 publications
1
89
0
Order By: Relevance
“…In addition, not only the presence of specific gene transcripts but also the magnitude of gene induction are likely to be important, with the latter not fully taken into account by GSEAs. In humans, sampling injection sites is difficult, although emerging micro-sampling techniques may provide new avenues [ 212 ]. Ultimately RNA-Seq of injection sites in animal models should be able to provide early warnings in the vaccine development process of potential reactogenicity issues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, not only the presence of specific gene transcripts but also the magnitude of gene induction are likely to be important, with the latter not fully taken into account by GSEAs. In humans, sampling injection sites is difficult, although emerging micro-sampling techniques may provide new avenues [ 212 ]. Ultimately RNA-Seq of injection sites in animal models should be able to provide early warnings in the vaccine development process of potential reactogenicity issues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, not only the presence of specific gene transcripts but also the magnitude of gene induction are likely to be important, with the latter not fully taken into account by GSEAs. In humans, sampling injection sites is difficult, although emerging micro-sampling techniques may provide new avenues (Lei et al ., 2019). Ultimately RNA-Seq of injection sites in animal models should be able to provide early warnings in the vaccine development process of potential reactogenicity issues.…”
Section: Discussionmentioning
confidence: 99%
“…The use of plasma sampling using specially designed plasma extraction cards such as the ADX 100 has the potential to eliminate the hematocrit area bias and the hematocrit extraction bias for minimally invasive sampling strategies. However, the amount of blood to separate plasma is quite large (e.g., ADX 100 cards need about 100 μl of blood) and the widespread adoption for applications could be restricted due to the limited biological information that the plasma sample may provide 36 …”
Section: Hematocrit Extraction Biasmentioning
confidence: 99%
“…Different HCT levels may have a positive or negative impact on the recovery of a target analyte leading to undesirable bias, known as hematocrit extraction bias. [35][36][37] For some analytes, such as naproxen, high HCT levels are expected to trap the drug within the matrix buildup, leading to the observation of lower desorption from the spot, resulting in a lower recovery. 37 For volumetric absorptive microsampling (VAMS), two studies reported that the drug recovery levels of analytes were inversely correlated with HCT levels.…”
Section: Hematocrit Extraction Biasmentioning
confidence: 99%